Determination of the Best Interest of Unaccompanied Minors in Slovenia - Žakelj, Tjaša; Lenarčič, Blaž (Two Homelands, 2017)
The paper deals with underage “third-country” nationals or stateless persons without parents or a legal representative, referred to as unaccompanied minors (UAMs). In Slovenia UAMs may hold varied types of status, and each of these implies different legal provisions and practical determination of the best interest of the child. According to the UNHCR Convention on the Rights of the Child, the best interest of the child should be the primary consideration in all actions concerning children. This paper focuses on how the principle of the best interest of the child is included in the sectoral national legislation and in other formal regulations which determine procedures regarding and treatment of UAMs. In addition, the article examines how experts understand this principle and put it into practice in various formal procedures. To that end, the views of experts who adopt or implement legal provisions, as well as the views of the experts who support UAMs during the international protection application process and in their everyday lives will be examined. Članek se ukvarja z mladoletniki brez spremstva, to je z mladoletniki, ki so v pravni terminologiji opredeljeni kot mladoletni državljani tretjih držav in so na območju Slovenije sami, brez staršev ali zakonitega zastopnika. V Sloveniji imajo mladoletni migranti brez spremstva različne statuse, med katerimi vsak vsebuje različne zakonske določbe ter praktične določitve otrokovih najboljših koristi, ki naj bi bile usklajene s Konvencijo OZN o otrokovih pravicah. Članek ponuja tudi pregled vključevanja načela otrokovih najboljših koristi v nacionalno zakonodajo in druge formalne predpise, ki določajo postopke in obravnave omenjenih skupin otrok. Obenem obravnava način sprejemanja zakonskih ukrepov, njihovega izvajanja ali nadzorovanja ter kako strokovnjaki v različnih formalnih postopkih razumejo in določajo načelo najboljše koristi otroka.